Peningkatan Hasil Belajar PPKn Materi Perumusan dan Penetapan Pancasila Sebagai Dasar Negara Menggunakan Model Pembelajaran Picture and picture pada Siswa Kelas VIIA: Array - Edy Bambang Susanto (Citra Dharma Cindekia, 2022)
The use of learning media in schools is not optimized so that the motivation and attention of students when attending lessons is still low. Based on the daily test scores obtained, the class completeness is only 72.28. Therefore, the authors try to overcome these problems by utilizing learning media, through classroom action research (CAR). This study aims to describe the implementation of learning by utilizing Picture and picture learning media and to describe the increase in activities and learning outcomes of class VIIA students of SMP Negeri 6 Purwodadi. For this reason, this research design uses classroom action research whose activities consist of planning, implementing, observing and reflecting which are divided into two cycles. The subjects of this study were students of class VIIA SMP Negeri 6 Purwodadi Odd Semester 2018/2019 academic year as many as 32 students. Research data obtained by observation and test methods. The results showed that the use of Picture and picture in learning can increase student activity and learning outcomes. From the results of the action, the average value of student learning outcomes in cycle I was 79.91 and cycle II 83.56. This shows that the use of Picture and picture can improve student learning outcomes. For this reason, it is recommended for teachers to develop the ability to apply using learning media during learning.